Creativity and innovation of Ludruk performing art in Lamongan Regency: A case study of Sendakala Ludruk performing art - Setiawan, Budiana; Sudiyono, Sudiyono; Afifah, Wiwiek; Suryandoko, Welly; Wibowo, Slamet; Setyono, Heru (BAHASTRA, 2026)
Creativity and innovation in ludruk need to be done because this traditional art is already on the verge of extinction. The lack of regeneration of interested young people and changes in people's tastes are the dominant factors causing the extinction of Ludruk. Without creative efforts in packaging ludruk to be relevant to the current context, supported by innovations in the presentation and use of technology, this cultural heritage is at risk of being lost in the next decade. This research aims to find out the creativity and innovation that needs to be done to preserve Ludruk art performances. The research method applied is qualitative. The research location is in the Ludruk Lamongan community. Data collection techniques include observation, interviews, and focused discussions. The results of the study showed that the creativity carried out by the Sendakala community included intensive practice before the performance; preparation of the manuscript as a guide for conducting dialogues; shortening of the duration of the show; colossal Ludruk performances; and collaboration with other Ludruk communities. Innovations include the dissemination of Ludruk art performances to schools; management improvement where there is a division of duties between stage directors, music directors, and dance directors; the use of technology to support the background of the scene; and the use of publications through social media. The creativity and innovation carried out by the Sendakala group is part of the revitalization effort to preserve Ludruk art performances in Lamongan Regency.